Preparation and thermal decomposition of solid state cinnamates of alkali earth metals, except beryllium and radium - Chiaretto, AGZ; Carvalho, MAD; Fernandes, N. S.; Ionashiro, M. (Editora Unesp, 1998)
Solid state compounds of general formula ML2.nH2O [where M is Mg, Ca, Sr or Ba; L is cinnamate (C6H5 -CH-CH-COO-) and n = 2, 4, 0.8, 3 respectiveiy] have been synthetized, Thermogravimetry (TG), derivative thermogravimetry (DTG), differential scanning calorimetry (DSC) and X-ray diffraction powder patterns have been used to characterize and to study the thermal stability and thermal decomposition of these compounds.
Keywords: alkali earth metals; cinnamate; thermal decomposition